AGENTS USED FOR ENAMEL REMINERALISATION AND REDUCING DENTIN HYPERSENSITIVITY: A COMPREHENSIVE REVIEW - N.V. Yanko (Проблеми екології та медицини)
ремінералізація, гіперчутливість, десенситизація, емаль, дентинRemineralisation agents not only strengthen enamel resistance, but also can occlude dentine tubules, reducing teeth sensitivity. This article provides an overview of various available agents used for enamel remineralisation and dentin hypersensitivity treatment. Conventional fluorides are used in the form of solutions, varnishes, foam, gels, dentifrices, showing low remineralising and desensitising ability as compared to newer fluoride-content products. Deep fluoridation is an effective method for reducing dentin hypersensitivity for a long time; its remineralising potential is used for white spot lesions treatment, caries prevention, and fissure sealing. Most novel fluoride compounds showed higher remineralising and desensitising abilities as compared to conventional fluorides. Deep penetration fluoridation is an effective method for remineralisation and reducing dentin hypersensitivity in long time. Despite of the fact that calcium phosphate systems have demonstrated a benefit over conventional fluorides in remineralisation their desensitising ability was not confirmed by various studies. The use of bioactive glass in remineralisation and desensitisation is quite promising, but further researches need to be undertaken to prove its efficacy. «Curodont» and synthetic nanohydroxyapatite from biomimetic systems showed good results in the above-mentioned treatments, but more researches are required to confirm their clinical efficacy. There is no doubt that iontophoresis with calcium and fluoride substances is still the most effective method in the office remineralisation, however, its potential effect in desensitisation has to be better evaluated. Efficacy of different kinds of lasers alone or in combination with a remineralisation agent has been confirmed mostly in vitro studies, therefore, there is a lack of clinical trials to prove their benefit. In latter studies, dentin sealants and desensitisers occluded dentin tubules were superior to conventional fluorides and synthetic nanohydroxyapatites. Simultaneously, the data about calcium phosphate and deep penetration fluoridation efficacy over such desensitisers as dentin sealants and nerve sensitivity inhibitors are controversial and indicate that additional studies are required to deepen our knowledge of the insufficiently explored area of reducing dentin hypesensitivity. In spite of the new advances, the ideal treatment modality for remineralisation does not exist. Within last decades, dentistry has made significant steps towards the elusive goal of enamel remineralisation and dentin desensitisation, but more long-term сlinical controlled studies are needed to confirm and quantify these findings, as well as to identify additional factors that can potentiate these processes.